Розробка компонентів інформаційної системи для доставки індивідуальних раціонів харчування - Комзолов, М. О. (ХНУРЕ, 2024)
This project is devoted to the development of components of a highly loaded information system for the delivery of individualized diets. Such a system allows the user to create an individual diet from the provided products and ready-made meals, as well as to arrange regular delivery of such a diet or the proposed diet to his or her place anywhere in the city. A multi-level architecture was used. This choice allows to greatly simplifies the testing phase of the system. User interaction with such a system will be possible through a website on the Internet.
Keywords: інтерфейс користувача; база даних раціонів; система замовлень; управління доставкою; планування меню